Recent Sprawl and Shrinkage Policies Deployed in The Sphere of Urban Management in Turkey: The Case of Ankara - Ahmet Tanju Gültekin (European Regional Science Association (ERSA), 2014)
In today's cities of Turkey, central as well as local urban administrations cannot succeed in attaining the power for planning the developmental trends and/or controlling the future along with bringing solutions to socio-cultural and economic problems. The root cause for this issue lies in the political and economic policies that support the urban expansion which is focused on the ultimate target of increasing urban value. Specifically, massive, secure residential compounds and shopping-centers built during the last couple of decades, private educational facility complexes and business centers constructed during the last two years - all of which are located in areas at the farthest edges of the city - coupled with the urban regeneration implementations initiated on the basis of the arguments foreseeing to increase the quality of life in the areas which promise high profitability, indicate the disownment of the integrated and sustainable planning concept. This situation is kept on-going, through taking refuge in the described objectives of attaining success in urban competitions during the process of globalization, ascension to the European Union, democratization. Such objectives, enforced by laws as of the year 2004, are simultaneously put into implementation partially through the mediation of the existing public bodies and partially through the mediation of new investors in the form of urban sprawl and shrinkage that mostly remain inert and unproductive. This, eventually, is an extension of the deindustrialization trends of neo-liberalism movements dating back to the 1980s. The persistent attitudes of the new political and economic power, backed up by legal, of the subject matter, legitimize the disintegrated planning system that slides over to the vision of increasing the urban value rather than public benefit and the concept of imperative management style, or, in other words, urban management is being handed over to the prioritized profitability concerns. This paper will evaluate this circumstance which the urban management in Turkey has been undergoing and which shapes urban development (or-non-development) through implementation examples realized in Ankara, the Capital city of the country.
Keywords: 330; urban management; urban sprawl and urban shrinkage; Ankara-Turkey